PIJR 2019
DOI: 10.36106/paripex/1901072
|View full text |Cite
|
Sign up to set email alerts
|

Role of antenatal betamethasone in premature babies and its effect on retinopathy of prematurity

Abstract: Background: advances in medical science has increase the overall survival rate of human being. this applies to neonates who born before their complete development in womb and their increased survival rate lead to increase occurrence rate of retinopathy of prematurity (ROP). In the struggle of their survival many measures done and one of which is injection of betamethasone to pregnant mother at the time of their premature delivery to develop their lungs and to reduce mortality. Materials and Methods: this is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…In our study;there was no factually critical contrast between bunch 1 and gathering 2 as respects sex, head periphery, and temperature inside 1 hour On the other hand; there was huge measurable increment of ROP among lower GA and BW.In concur with,Ghelaniet al, [8] who foundthat sexual orientation was not found as a danger factor for ROP. Hwang et al, [9] revealed that; all newborn children who created ROP in their investigation weighed <1,750 g upon entering the world.…”
Section: Discussionsupporting
confidence: 84%
“…In our study;there was no factually critical contrast between bunch 1 and gathering 2 as respects sex, head periphery, and temperature inside 1 hour On the other hand; there was huge measurable increment of ROP among lower GA and BW.In concur with,Ghelaniet al, [8] who foundthat sexual orientation was not found as a danger factor for ROP. Hwang et al, [9] revealed that; all newborn children who created ROP in their investigation weighed <1,750 g upon entering the world.…”
Section: Discussionsupporting
confidence: 84%